2015
DOI: 10.1111/cts.12256
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Profiling of Sinus Mucosa from Patients with Chronic Rhinosinusitis

Abstract: Sinusitis is a cause of significant morbidity, substantial healthcare costs, and negative effects on quality of life. The primary objective of this study is to characterize the previously unknown lipid profile of sinonasal mucosa from patients with chronic rhinosinusitis (CRS) and from controls. Sinus mucosa samples were analyzed from 9 CRS patients with concomitant nasal polyps, 11 CRS patients without polyps, and 12 controls. Ten lone polyp samples were also analyzed. Samples were subjected to a modified Bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Metabolomics analysis of low molecular weight compounds (up to 1,500 Da) has been performed in CRS 83 . Fazlollahi et al found that fatty acids (palmitic, oleic, stearic, and lauric) were highly elevated in CRSwNP compared to CRSsNP and control tissues 86 . Miyata found impaired synthesis of cyclooxygenase-and lipoxygenase-derived mediators (including prostaglandin D 2 [PGD 2 ], PGE 2 , thromboxane B 2 , 15-hydroxyeicosatetraenoic acid and lipoxin A 4 ) and selective upregulation of leukotriene D4 in nasal polyp-derived eosinophils compared to healthy peripheral blood eosinophils 87 .…”
Section: Genomics Proteomics and Metabolomicsmentioning
confidence: 98%
“…Metabolomics analysis of low molecular weight compounds (up to 1,500 Da) has been performed in CRS 83 . Fazlollahi et al found that fatty acids (palmitic, oleic, stearic, and lauric) were highly elevated in CRSwNP compared to CRSsNP and control tissues 86 . Miyata found impaired synthesis of cyclooxygenase-and lipoxygenase-derived mediators (including prostaglandin D 2 [PGD 2 ], PGE 2 , thromboxane B 2 , 15-hydroxyeicosatetraenoic acid and lipoxin A 4 ) and selective upregulation of leukotriene D4 in nasal polyp-derived eosinophils compared to healthy peripheral blood eosinophils 87 .…”
Section: Genomics Proteomics and Metabolomicsmentioning
confidence: 98%
“…Fazlollahi et al [22] demonstrated the application of an untargeted lipidomic study for the analysis of lipids, among other metabolites. The levels of fatty acids were, on average, 10-fold higher in CRS patients with concomitant NP growth compared to other groups, which suggested an altered lipid metabolism in the sinus mucosa samples.…”
Section: Chronic Rhinosinusitis (Crs)mentioning
confidence: 99%
“…Over the years, clinicians have identified several phenotypes of SA, based on the presentation, the age of onset of symptoms, the severity of the disease, and the presence of other conditions such as allergic status and/or eosinophilia, with different long-term outcomes, rate of exacerbations and response to therapy with corticosteroids [22].…”
Section: Biomarker Research In Type 2 Severe Asthmamentioning
confidence: 99%
“…Fazlollahi et al [ 21 ] demonstrated the application of an untargeted lipidomic study for the analysis of lipids among other metabolites. The authors assessed sinonasal tissue samples (sinus mucosa) from 9 patients with CRS with concomitant NP, 11 patients with CRS without polyps, and 12 healthy controls.…”
Section: Metabolomics In Searching For Crs-related Metabolitesmentioning
confidence: 99%
“…Many different bioinformatics tools have been developed to aid research in this field, such as optimizing the storage and accessibility of proteomic data or statistically ascertaining the significance of protein identification [ 19 , 20 ]. Based on metabolomic studies, the metabolic fingerprinting strategy [ 21 ], metabolic profiling, and quantitative targeted metabolomics are identified as useful in CRS development [ 22 , 23 ]. Each of the presented studies has utilized different strategies as well as specific, modern, highly sensitive analytical instrumentations.…”
Section: Introductionmentioning
confidence: 99%